Influence of biocontrol agents and fungicides on vegetative parameters of groundnut (Arachis hypogaea L.) under greenhouse conditions: INFLUENCE OF BIOCONTROL AGENTS & FUNGICIDES ON VEGETATIVE PARAMETERS OF GROUNDNUT - S AMEER BASHA; G RAGHAVENDRA; A V RAMANJANEYULU; A SRINIVAS (Journal of Oilseeds Research, 2016)
In the present study the compatibility of various plant growth promoting organisms [Pseudomonas fluorescens (Pf), Trichoderma viride (Tv) and Rhizobium (Rhi)] along with fungicides (mancozeb, tebuconazole and carbendazim + mancozeb) was tested on groundnut crop (cv. K-6) variety under greenhouse conditions. At 45 days after sowing (DAS), maximum (109) number of root nodules was observed in plants treated with combination of biocontrol agents Pf, Tv and Rhi. Maximum (1314.7 mm) root length was observed in Pf and Rhi combination while root area was recorded to be maximum (1341.8 mm2) in Rhi treatment. Root diameter (3.7 mm), root hairs (79.5) and chlorophyll content (51.7) were significant in Pf and Rhi combination. At 90 DAS, boosting effect on root nodules with maximum number (111) was seen in seeds treated with combination of biocontrol agents Pf, Tv and Rhi. Root length was prominent (1775.5 mm) in Tv treated plants whereas root area was maximum (1865.6 mm2) in Pf and Rhi combination. Maximum root diameter (4.8 mm) was found in Pf and Rhi combination whereas Pf, Tv and Rhi combination showed significant (108.5) root hair number. Pf treated plants showed remarkable (60.3) chlorophyll content compared to other treatments. The study showed increase in overall growth parameters in biocontrol agents treated plants followed by fungicides.